The Royal Range - Flanagan, John (New York, NY Philomel Books, an imprint of Penguin Group (USA), 2013)
Will Treaty is a shell of his former self, and his first apprentice may be the only one who can save him
1
Keywords: Apprentices -- Juvenile fiction; Fantasy